2022
DOI: 10.1007/s11695-022-06386-1
|View full text |Cite
|
Sign up to set email alerts
|

Patients with a History of Bariatric Surgery Are 8 Years Younger at Presentation with Severe Alcoholic Hepatitis

Abstract: Purpose Patients with prior bariatric surgery (BS) are at risk to develop alcohol use disorder (AUD) and alcohol-related liver disease (ALD). Severe alcoholic hepatitis (sAH) is one of the most severe manifestations of ALD with a 28-day mortality of 20-50%. The impact of prior BS on patients presenting with sAH was assessed. Methods From 01/2008 to 04/2021, consecutive patients admitted to a tertiary referral center with biopsy-proven sAH were included in a database. Results One hundred fifty-eight sAH patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The liver decompensation was also more severe in the patients with a prior BS (56). A recent study reported similar data of BS patients presenting at a younger age with acute alcoholic hepatitis (57). In a retrospective observational analysis of obese adults based on insurance claims, women had undergone BS had twofold increased risk of alcoholic cirrhosis and alcohol misuse compared to women without prior surgery (58).…”
Section: Impact Of Bariatric Surgery On Liver Functionmentioning
confidence: 65%
“…The liver decompensation was also more severe in the patients with a prior BS (56). A recent study reported similar data of BS patients presenting at a younger age with acute alcoholic hepatitis (57). In a retrospective observational analysis of obese adults based on insurance claims, women had undergone BS had twofold increased risk of alcoholic cirrhosis and alcohol misuse compared to women without prior surgery (58).…”
Section: Impact Of Bariatric Surgery On Liver Functionmentioning
confidence: 65%
“…Although BS patients were younger at presentation, survival was similar (61). In a retrospective observational analysis of obese adults based on insurance claims, women had undergone BS had twofold increased risk of alcoholic cirrhosis and alcohol misuse compared to women without prior surgery (62).…”
Section: Post-operative Management -Monitoring Liver Functionmentioning
confidence: 95%
“…Similarly, a recent study reported that a history of BS is increasingly common in patients presenting with acute alcoholic hepatitis. Although BS patients were younger at presentation, survival was similar [ 61 ]. In a retrospective observational analysis of obese adults based on insurance claims, women had undergone BS had twofold increased risk of alcoholic cirrhosis and alcohol misuse compared to women without prior surgery [ 62 ].…”
Section: Bariatric Surgery In Cirrhosis and Context Of Liver Transpla...mentioning
confidence: 99%
“…Bariatric surgery is associated with an increased risk of alcohol-related liver disease (e.g., alcohol hepatitis and cirrhosis) and AUD-related hospitalizations. 3,[19][20][21][22][23] Despite the increasing number of studies on this topic, few qualitative studies exist. Most of these have focused on patient-perceived causes of postoperative AUD.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have also found a higher incidence of AUD‐related diseases after bariatric surgery. Bariatric surgery is associated with an increased risk of alcohol‐related liver disease (e.g., alcohol hepatitis and cirrhosis) and AUD‐related hospitalizations 3,19–23 …”
Section: Introductionmentioning
confidence: 99%